The Effects of Urban Pollution on the “Gesù Nuovo” Façade (Naples, Italy): A Diagnostic Overview - Alessandro De Rosa; Paola Cennamo; Chiara Saltarelli; Giorgio Trojsi; Juri Rimauro; Maria Rosaria Vigorito; Elena Chianese (Atmosphere)
The deterioration of stone heritage in urban environments is mainly the product of sources of air pollution like vehicular traffic and domestic heating. The results of these phenomena usually manifest as acid rain and particulate patinas, acting on the surface of stone monuments to form the so-called “black crusts”, a typical stone degradation product, mainly composed of gypsum. The aims of this study were to investigate the extent of these phenomena on the decorative apparatus of the frontal façade of Gesù Nuovo Church, in the historical centre of Naples (Italy). Preliminary diagnostics consisted of XRD and FTIR to analyse the composition of stone materials and inquire about previous restorations. The chemical characterization of black crusts was performed, using a diverse array of techniques, to highlight how different compounds are distributed along a vertical gradient and considering the proximity of specific sources of pollution (vehicle engine ignition, incense combustion, domestic heating products). Finally, molecular biology techniques were employed to identify the organisms which typically dwell in this formation and speculate about their contribution to the degradation of stone.